Physiotherapist-led musculoskeletal education: an innovative approach to teach medical students musculoskeletal assessment techniques - Boulila, Cyril; Girouard-Chantal, Élise; Gendron, Christophe; Lassman, Matthew; Dubé, Timothy (Canadian Medical Education Journal, 2021)
Implication Statement We developed physiotherapist-led interprofessional (IP) workshops for medical students each dedicated to a specific anatomical region. The workshops alternated between theoretical presentations from a physiotherapist about basic musculoskeletal (MSK) assessment techniques and hands-on practice in small groups with feedback from Master’s-level physiotherapy students (MPT). The workshops created an optimal IP learning environment where medical students can learn MSK assessment techniques and MPTs can apply their knowledge and clinical skills. Academic institutions with physiotherapy and medical programs seeking to develop IP learning activities should foster opportunities for IP collaboration between physiotherapy and undergraduate medical education.